The Implementation of a Body Mass Index (BMI) Calculator in an Android-Based Ideal Body Check and Nutrition Consultation Application - Ardiansyah, Diky; Avianto, Donny (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The rising prevalence of obesity necessitates the development of effective strategies for personalized nutritional guidance. This study aims to address common barriers to accessing nutritional advice, such as geographic distance, time constraints, and financial limitations, by introducing an innovative mobile application. The application incorporates a Body Mass Index (BMI) calculator for ideal weight estimation and a real-time online consultation feature with certified nutrition counselors. A user-centered design methodology was employed to ensure the app's usability, accessibility, and engagement. The findings reveal that the app effectively facilitates healthier lifestyle adoption by providing personalized nutritional recommendations and fostering user motivation through regular updates, reminders, and progress-tracking tools. Additionally, the application enhances community engagement by disseminating evidence-based nutritional practices at individual and societal levels. This research highlights the potential of the application as a scalable solution for bridging the gap between users and professional nutritional advice. By empowering individuals to make informed health decisions, the app contributes to obesity prevention and the promotion of a healthier society. Future studies should investigate its long-term effects on health outcomes and explore the integration of advanced features to further enhance its functionality and impact.